2019
DOI: 10.1002/open.201800284
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐Stacking Water Clusters: Morphology and Stabilities

Abstract: The structures and interaction energies of water clusters with ring stacking motifs are studied by using ab initio calculations. The structures of the water clusters are constructed by stacking either single rings or multi‐rings of tetramer, pentamer, and hexamer. We found that, in the single‐ring‐stacking motif, the most stable isomers exhibit an alternative clockwise‐anticlockwise stacking pattern. We also show that four‐layer single‐ring‐stacking isomers are not energetically favorable in comparison with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
(233 reference statements)
3
7
0
Order By: Relevance
“…Thus, stable clusters of water molecules should be expected to have at least three hydrogen bonds per molecule. Along these lines, our results could be interpreted within the framework of a recent theoretical investigation of lowest-energy structures of water clusters consisting of arranged or single rings or multiple rings of tetramer, pentamer and hexamer (41). The authors have shown that, when single-ring stacking structures have more than 3 layers, the number of weak hydrogen bonds among the layers increases, thus reducing the stability of the stacked structure.…”
Section: Structuring Of Water Clusterssupporting
confidence: 62%
“…Thus, stable clusters of water molecules should be expected to have at least three hydrogen bonds per molecule. Along these lines, our results could be interpreted within the framework of a recent theoretical investigation of lowest-energy structures of water clusters consisting of arranged or single rings or multiple rings of tetramer, pentamer and hexamer (41). The authors have shown that, when single-ring stacking structures have more than 3 layers, the number of weak hydrogen bonds among the layers increases, thus reducing the stability of the stacked structure.…”
Section: Structuring Of Water Clusterssupporting
confidence: 62%
“…The averaged bond length of H-bonds in the (H 2 O + O 2 )/p-Gra complex is 2.26 Å, which is close to H-bonds in water clusters. 47,48 To further understand the property of co-adsorption of H 2 O and O 2 on pentagraphene, total and partial density of states are calculated and depicted in Fig. 7(c).…”
Section: Interactions and Electronic Properties Of Molecules On Penta...mentioning
confidence: 99%
“…Fragments, three-dimensional cage-like building blocks constituted by rings, can elucidate the heterogeneity of hydrogen bond structures and rearrangements 34 . Topologically, water clusters also comprise small cyclic water clusters such as tetramers, pentamers and hexamers 39 , 40 . The topology of water clusters strongly affects the structure and chemistry of clusters 41 , 42 .…”
Section: Introductionmentioning
confidence: 99%